Spatial Profile of the Dead Core for the Fast Diffusion Equation with Dependent Coefficient - Zhengce Zhang; Biao Wang (International Journal of Differential Equations)
We consider the dead-core problem for the fast diffusion equation with spatially dependent coefficient and obtain precise estimates on the single-point final dead-core profile. The proofs rely on maximum principle and require much delicate computation.